Strategi Bank Syariah Indonesia Meningkatkan Inklusi Keuangan - Oktavia, Novi Tri (STAI Auliaurrasyidin Tembilahan, 2023)
This research is motivated by the efforts made by Bank Syariah Indonesia in participating in increasing financial inclusion in Indonesia. The development of financial inclusion in Indonesia has been slow due to the low financial literacy of the community. Therefore, researchers sought to conduct this research with the aim of describing the form of efforts made by Bank Syariah Indonesia in encouraging financial inclusion in Indonesia. This research was conducted in Malang City, especially at BSI KC Malang Soetta and BSI KC Malang Sutoyo using qualitative research methods and case study research types. The results obtained by the researcher are BSI KC Malang Soetta and BSI KC Malang Sutoyo using BSI Mobile to facilitate customers in accessing remote financial services. In introducing programs and services on BSI Mobile, BSI socialised BSI Mobile by holding a Mata Najwa On Stage event spearheaded by renowned journalist Najwa Shihab. The socialisation event was held at the UMM Dome on Wednesday, 12 July 2023.